How does interpersonal curiosity impact peer rejection? The mediating effect of relative deprivation and malicious envy - He, Jiali; Liu, Hanshu (Frontiers in Developmental Psychology, 2024)
Objective: Peer rejection is one of the key indicators for measuring interpersonal relationships for adolescents. Considering that interpersonal curiosity plays a significant role in interpersonal relationships. But the influence of interpersonal curiosity on peer rejection is still unknown. This study is grounded in social comparison theory and aims to investigate the impact of adolescent interpersonal curiosity on peer rejection. The study explores the impact of interpersonal curiosity on peer rejection and further investigates the mediating role of relative deprivation and malicious envy. Methods: The study employed the stratified cluster sampling method to select 418 adolescents in Shaanxi Province. The Adolescents' Relative Deprivation Scale was used to measure relative deprivation, the Benign and Malicious Envy Scale was used to measure benign envy and malicious envy, and the School Adaptation Inventory was used to measure peer rejection. The statistical software SPSS 24.0 and AMOS 24.0 were used for statistical analysis, and the common method deviation test was conducted using the Harman single-factor control method. Finally, the bootstrap sampling method was used to test the significance of the intermediary effect. Results: The results of the mediation model show that interpersonal curiosity can directly and positively affect peer rejection (β =0.317, p < 0.001); Malicious envy plays a completely mediating role (b= 0.125, p < 0.001), while relative deprivation plays a partially mediating role (b direct-path = 0.071, p = 0.004; b indirect-path = 0.064, p < 0.001). Further discovery of the chain mediation model show that interpersonal curiosity can impact individual peer rejection through the chain mediation of relative deprivation and malicious envy (b= 0.026, p < 0.001), and there is no significant gender difference in this result. Conclusions: Interpersonal curiosity can enhance peer rejection in adolescents, with relative deprivation and malicious envy completely mediating this process. This study reveals the impact of interpersonal curiosity on adolescent’s peer rejection from the viewpoint of social comparison theory and provides a new perspective for fostering the formation and growth of positive peer relationships among adolescents.